Pengaruh Kualitas Daya Tarik Wisata Terhadap Kepuasan Wisatawan di Puncak Becici Yogyakarta - Heni Dwi Lestari (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to determine the effect of tourist attraction quality on tourist satisfaction at Becici Peak, Yogyakarta. The research method used is quantitative with simple linear regression analysis with the independent variable of tourist attraction quality and the dependent variable is tourist satisfaction. Data were collected through distributing questionnaires to 100 tourist respondents at Becici Peak, Yogyakarta. The results showed that the quality of tourist attractions had a positive and significant influence on visitor satisfaction at Becici Peak by 68.3%, the remaining 31.7% was influenced by other variables not examined in this study. This study provides practical implications for Becici Peak managers in improving the quality of tourist attractions to increase visitor satisfaction.